Дослідження впливу змивів з полів на виникнення процесу евтрофікації водозаборів - Костенко, В. К.; Таврель, М. І. (Луцький національний технічний університет, 2025)
Метою даного дослідження є розкриття механізму впливу зміни вмісту поживних речовин у хімічному складі водних біотопів на життєдіяльність ціанобактерій, зокрема їх розвиток та розмноження при наявності мінеральних добрив, таких як азот, фосфор і калій.

The goal of this study is to reveal the mechanism of the impact of changes in the nutrient content of the chemical composition of aquatic habitats on the life activity of cyanobacteria, particularly their development and reproduction in the presence of mineral fertilizers such as nitrogen, phosphorus, and potassium. Research Pethodology. Experimental methods were used to conduct the research, including
Research on the impact of field runoff on the occurrence of the eutrophication process of water intakes
Keywords: мінеральні добрива; ціанобактерії; біоценоз; штучний біотоп; евтрофікція; mineral fertilizers; cyanobacteria; biocenosis; artificial habitat; eutrophication